Vortex-induced vibration of large deformable underwater composite beams based on a nonlinear higher-order shear deformation zig-zag theory. (15th April 2022) - Liu, Hao; Qu, Yegao; Xie, Fangtao; Meng, Guang
Abstract: Vortex-induced vibration (VIV) of a flexible composite laminated beam rigidly attached to a circular cylinder in underwater flow is investigated. A general higher-order shear deformation zig-zag theory combined with von Kármán strains is adopted to characterize the geometrical nonlinearity of the composite laminated beam. A strongly coupled, partitioned fluid-structure interaction method based on an Arbitrary Lagrangian-Eulerian (ALE) approach is employed to accommodate the evolution of the fluid domain and the dynamic coupling of the fluid and the structure. The validity of the present method is confirmed. The discrepancies in the results of the VIV of isotropic and composite laminated beams determined by different beam theories are investigated. The effects of the fiber orientation and inflow velocity on the VIV characteristics (including limit-cycle oscillation, vortex shedding frequency, and flow pattern) of composite laminated beams are discussed. Four distinct deformation configurations of composite beams are observed, i.e., the first mode-like vibration shape, double-frequency vibration shape, second mode-like vibration shape, and lower-frequency large magnitude oscillation shape. Different deformation shapes lead to differences in the wake vortex modes, including the 2S (two single vortices with opposite signs) and the 2P (two pairs of vortices) wake vortex mode. Highlights: A general higher-order shear deformation zig-zag theory is developed. Vortex-induced vibration behaviors of composite laminated beams are analyzed. Effects of the fiber orientation and inflow velocity on the vortex-induced vibration characteristics are examined. Physical insight into limit-cycle oscillation, vortex shedding frequency, and flow pattern is provided.